2016
DOI: 10.18632/oncotarget.12924
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 mediates MYCN control of epithelial-mesenchymal transition through silencing of metastatic suppressor NDRG1 gene

Abstract: Neuroblastoma (NB) with MYCN amplification is a highly aggressive and metastatic tumor in children. The high recurrence rate and resistance of NB cells to drugs urgently demands a better therapy for this disease. We have recently found that MYCN interacts with the lysine-specific demethylase 1 (LSD1), a histone modifier that participates in key aspects of gene transcription. In cancer cells, LSD1 contributes to the genetic reprogramming that underlies to Epithelial-Mesenchymal Transition (EMT) and tumor metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 45 publications
(61 reference statements)
0
40
0
Order By: Relevance
“…Again, we used bioinformatics tools to explore such putative links and performed a meta-analysis of the protein interactants potentially linking the identified candidate cytokines with N-Myc. Indeed, a well identified mechanism of NDRG1 repression relies on the binding of N-Myc to the promoter region of NDRG1 and the subsequent recruitment of histone deacetylases leading to promoter hypermethylation and an epigenetic silencing of NDRG1 [47][48][49][50][51][52]. Our meta-analysis showed that only TGFBR1 (an oligodendrocyte-expressed receptor to TGFB1) and PDGRA (an oligodendrocyte-expressed receptor to PDGFC) formed a close (second shell) protein network with N-MyC.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Again, we used bioinformatics tools to explore such putative links and performed a meta-analysis of the protein interactants potentially linking the identified candidate cytokines with N-Myc. Indeed, a well identified mechanism of NDRG1 repression relies on the binding of N-Myc to the promoter region of NDRG1 and the subsequent recruitment of histone deacetylases leading to promoter hypermethylation and an epigenetic silencing of NDRG1 [47][48][49][50][51][52]. Our meta-analysis showed that only TGFBR1 (an oligodendrocyte-expressed receptor to TGFB1) and PDGRA (an oligodendrocyte-expressed receptor to PDGFC) formed a close (second shell) protein network with N-MyC.…”
Section: Discussionmentioning
confidence: 98%
“…Since then, in multiple cell types, MYCN was shown to silence NDRG1 gene expression via a process involving a hypermethylation of the NDRG1 promoter [47][48][49][50][51][52] . On this basis, we performed a meta-analysis of the human interactome to determine whether signaling pathways could link MYCN to the identified candidate molecules (i.e IL17D, IL33, IL12A, PDGF-C and TGFB1).…”
Section: Identification Of a Molecular Pathway Linking Mycn To Pdgfc mentioning
confidence: 99%
“…Additionally, we observed that the half‐life of LSD1 is decreased from an initial 30 h to 21 h after HCI‐2509 treatment. This is in agreement with previous studies with respect to neuroblastoma and prostate cancer (Ambrosio et al ., ; Sehrawat et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that demonstrates that 8-oxoGua generation may regulate transcriptional activation, derived from experiments involving estrogen-responsive genes, Myc targeted genes and hypoxia-inducible genes [48][49][50][51]. It was demonstrated that exposure of cells to estrogen substantially increases 8-oxoGua in the promoter region of estrogen-responsive genes, which in turn recruits OGG1 and topoisomerase IIβ.…”
Section: Potential Regulatory Role Of 8-oxoguamentioning
confidence: 99%
“…OGG1 generates transient nicks, which allows entry of the topoisomerase, the activity of which relaxes the DNA strand, triggering chromatin conformational changes essential for estrogen-induced transcription [48]. It has been shown that a similar mechanism is responsible for Myc-induced transcription activation [50]. It is proposed that upon binding of above mentioned transcription factors to the specific sequences, demethylating enzyme lysine-specific demethylase 1 (LSD1) is recruiting.…”
Section: Potential Regulatory Role Of 8-oxoguamentioning
confidence: 99%